If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6g + 3(-5 + 4g) = 1 + -1g 6g + (-5 * 3 + 4g * 3) = 1 + -1g 6g + (-15 + 12g) = 1 + -1g Reorder the terms: -15 + 6g + 12g = 1 + -1g Combine like terms: 6g + 12g = 18g -15 + 18g = 1 + -1g Solving -15 + 18g = 1 + -1g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add 'g' to each side of the equation. -15 + 18g + g = 1 + -1g + g Combine like terms: 18g + g = 19g -15 + 19g = 1 + -1g + g Combine like terms: -1g + g = 0 -15 + 19g = 1 + 0 -15 + 19g = 1 Add '15' to each side of the equation. -15 + 15 + 19g = 1 + 15 Combine like terms: -15 + 15 = 0 0 + 19g = 1 + 15 19g = 1 + 15 Combine like terms: 1 + 15 = 16 19g = 16 Divide each side by '19'. g = 0.8421052632 Simplifying g = 0.8421052632
| (90000*0.5326-5150)/1000*31.91= | | 4(2+3x)=3(2x+5) | | 32-8x=-45 | | 5n=115 | | 3(x-2)-2x=-12 | | 3j=15J-14 | | (140000*0.5534-5400)/1000*34.84= | | 99=x+86 | | cos(8x)=-1 | | 2x^5+3x^4+6x^3+20x^2+60x-36=0 | | (160000*0.5501-4400)/1000*28.44= | | 5c-4c+666+55=43556n | | -3x+4y=-10 | | -9=m-2 | | 2x^5+3x^4+6x^3+2-x^2+60x-36=0 | | 4a-5(a-2)= | | n-2-5n=3n-56 | | 6x-15=-63 | | (160,000*0.5501-4400)/1000*28.44= | | -11+b=11 | | 1.5a+0.25a-0.75a=-10 | | 0.5x-0.2y=1.2 | | 2=2x-14 | | 9x-10=3x+74 | | 20=3x^2 | | 3x+40=8x | | 12x+19=7x+154 | | (200,000*0.5337-4600)/1000*34.83= | | 2x+5y-8x+12y= | | a=6(4+1/2)2 | | x-52=5 | | 8x-1=5x+41 |